Exchange Rate Politics in Latin America - Wise, Carol (Book collections on Project MUSE., 2011)
Most of the analysis of Latin American exchange rate problems and policies has concentrated on the economic side of things. This volume instead examines the politics of exchange rate management in four nations that had very different approaches and results. Although the Mexican peso crash, Brazil's currency crisis, Argentina's maintenance of a currency board, and Venezuelan policy responses to the shocks of 1997-98 have had major international financial ramifications, the origins and outcomes of these dramatic events have yet to be analyzed in a single volume. The contributors tie these policy.